Integrate for car brake failure and engine overheat system - G. Subhashini; Anas Aiman Albanna; Raed Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
One of the most important features in a car is its braking system and engine. The braking system enables the driver to control the speed of the vehicle when the need arises in order to protect the car, driver and other road users from accidents which might be fatal. The performance of the entire car also relies largely on the effective delivery and operation of the car engine whose ability to deliver the required performance is hinged on its temperature. In recent years a variety of IOT based monitoring and control systems have been explored in various areas of modern technology. This Final Year research project proposes the design and development of an IOT based vehicle brake failure and engine overheating system. The proposed system utilizes a network of sensors to monitor the temperature of the car engine, obstacles along the path of the car and the speed of the vehicle. The sensor data retrieved from the monitoring system is used by the control system consisting of a microcontroller to make decisive automatic decisions for the vehicle brake and failure system. A warning system consisting of LCD, Buzzer and LED has also been added into the system to warn the driver regarding the operation of the braking and engine overheating system. Two microcontrollers have been utilized for this research i.e. Arduino Uno for sensor data acquisition and processing and a Raspberry Pi microcontroller for purposes of sending the data wirelessly to a web platform. The web platform developed enables the user to remotely access real-time and past data from the system vehicle brake failure and engine overheating system. A variety of tests were conducted on the system to evaluate its performance whereby 95.4% accuracy was achieved in in terms of the ability of the car to effectively and automatically brake in the presence of obstacles and in terms of speed control. Testing done on the ability of the system to accurately monitor the engine temperature shows that its able to achieve 97.5% accuracy. The IOT system is able to transmit the sensor data retrieved from the system using both WIFI and mobile data whereby an average transmission time of 2.32 s and 4.33 s was recorded for each system respectively.